Effect of intra-abdominal pressure on maximum level of intrathecal sensory block: A preliminary randomized controlled trial - Jubin Jakhar; Michell Gulabani; Asha Tyagi; Ashok K Sethi (Wolters Kluwer Medknow Publications, 2023)
Objectives: Increase in Intra-Abdominal Pressure (IAP) is commonly accepted as a cause for intrathecal dose sparing and consequently higher level of sensory block during pregnancy. There is however very little actual data evaluating the relationship. Thus, we aimed to evaluate association between IAP and maximum level of sensory block following intrathecal injection of hyperbaric bupivacaine as well as plain levobupivacaine for cesarean section. Methods: Preliminary randomized controlled blinded trial included females aged 18-40 years, scheduled for elective cesarean section under single-shot subarachnoid block. After randomization, they received either intrathecal hyperbaric bupivacaine (group H) or plain (isobaric) levobupivacaine (group P) in a dose of 12.5 mg (n = 40 each). IAP was measured before and after the spinal block, using the recommended intravesical technique. The maximum level of sensory block and the IAPs were measured in each patient. Results: There was no significant correlation of IAPprespinal with maximum level of sensory block for group H (P = 0.334; rs = -0.157) or group P (P = 0.637; rs = -0.078). Similarly, there was no significant correlation of the IAPpostspinal: group H (P = 0.370; rs = -0.145); and group P (P = 0.714; rs = -0.061). Both group H and group P had similar IAPprespinal (15.9 [14.3-18.2] and 15.3 [14.3-17.4] mmHg, respectively) (P = 0.474); as well as IAPpostspinal (15.2 [13.8-17.2] and 14.6 [13.4-16.0] mmH, g respectively) (P = 0.239). Among ancillary observations, duration of sensory block was significantly longer for group P versus group H (133.6 ± 24.2 and 103 ± 23.4 mins; P < 0.000). However, the maximum levels of sensory and motor block, respective times required to achieve them, as well as incidences of intraoperative hypotension and bradycardia were statistically similar between group H and group P (P > 0.05). Conclusions: The IAP was raised to the level of conventionally defined intra-abdominal hypertension (>12 mmHg) in patients scheduled for elective cesarean section. However, despite being increased, the IAPprespinal or IAPpostspinal did not show any significant association with the maximum level of sensory block (P > 0.05).